SAHİB BİN ABBAD’S LİFE, PERİOD, ENVİRONMENT (Journal of Oriental Studies, 2016)
This article indicates that Sahib ibn Abbad who was prominent social, political, literary figure of l0th century lived and worked in Buveyhs Palace and was one of viziers of state. He was Muayyadidovle and Faxruddovle’s (Buveyhs state’s Rey part’s leader Rikuuddovle’s sons) vizier. He played great role in development of Buveyh’s state as a skilled statesman. Sahib ibn Abbad improved himself as a prominent social, political figure, writer and poet of his times by the power of this state. Sahib ibn Abbad was also prominent scientist of his time. Bin Abbad had always protected his honor and dignity, and saying viziers come after sultans he always considered himself the first. Because he appreciated himself not only Amirs but also scientist poet and writer. For example, when Nuh Ibn Mansur Samani knew about his famous invited him to his palace. But Sahib had rejected his proposal and he noted that he had never left his palace.
Keywords: Sahib bin Abbad; vizier; scientific; writer